Impact of Obesity on IL-12 Family Gene Expression in Insulin Responsive Tissues - Nam, Heesun (2012)
Mounting evidence has established a role for chronic inflammation in the development of obesity-induced insulin resistance, as genetic ablation of pro-inflammatory cytokines and chemokines elevated in obesity improves insulin signaling in vitro and in vivo. Recent evidence further highlights interleukin (IL)-12 family cytokines as prospective inflammatory mediators linking obesity to insulin resistance. In this study, we present empirical evidence demonstrating that IL-12 family related genes are expressed and regulated in insulin-responsive tissues under conditions of obesity. First, we report that respective mRNAs for each of the known members of this cytokine family are expressed within detectable ranges in WAT, skeletal muscle, liver and heart. Second, we show that these cytokines and their cognate receptors are divergently regulated with genetic obesity in a tissue-specific manner. Third, we demonstrate that select IL-12 family cytokines are regulated in WAT in a manner that is dependent on the developmental stage of obesity as well as the inflammatory progression associated with obesity. Fourth, we report that respective mRNAs for IL-12 cytokines and receptors are also expressed and divergently regulated in cultured adipocytes under conditions of inflammatory stress. To our knowledge, this report is the first study to systemically evaluated mRNA expression of all IL-12 family cytokines and receptors in any tissue under conditions of obesity highlighting select family members as potential mediators linking excess nutrient intake to metabolic diseases such as insulin resistance, diabetes and heart disease.